BRACHIAL-ANKLE PULSE WAVE VELOCITY IS INVERSELY ASSOCIATED WITH OBESITY IN A HEALTHY CHINESE POPULATION. (April 2021) - Zuo, Junli; Tang, Biwen; O'rourke, Michael; Avolio, Alberto; Adji, Audrey
Abstract : Objective: Obesity is generally considered undesirable on account of its association with metabolic syndrome and other risk factors for cardiovascular disease. However, obese subjects paradoxically appear to have better outcome following certain interventions (eg vascular interventions in heart failure) compared to non-obese subjects, suggesting a vascular protective effect of obesity (obesity paradox). This study aimed to quantify the association between indices of obesity and arterial stiffness as measured by brachial-ankle pulse wave velocity (baPWV) in a healthy Chinese population. Design and method: Normal individuals (n = 858) attending a health assessment clinic for cardiovascular disease screening at Ruijin Hospital North, Shanghai, China, between April 2017 and June 2018, had measurements of baPWV (Omron, BP-203RPEIII VP-1000) and brachial systolic (SP), diastolic (DP), mean (MP) and pulse pressure (PP). Subjects were divided into 3 groups according to their Body Mass Index (BMI, kg/m2): BMI less than 24, normal; 24–28, overweight; greater than 28, obese (using Chinese guidelines). Results: All brachial pressures were significantly higher as BMI increased. baPWV increased significantly when the normal group was compared with overweight or obese groups (p < 0.001). However, no differences were apparent between the overweight and obese group, with baPWV being lower in the obese group with higher BMI. Using baPWV as the independent continuous variable in multiple linear regression, age, MP and heart rate were all positively associated with baPWV, whereas BMI was negatively associated with baPWV after adjusting for confounding factors (β=-0.104, p < 0.001). A negative linear relationship between BMI class and baPWV was only apparent for males less than50 years (p = 0.01) and females of age above 50 years (p < 0.01). Conclusions: baPWV, as a measure of arterial stiffness, is higher for similar SP values in the normal individuals when compared to those in overweight and obese groups, consistent with the "obesity pardox". The disparate effects of BMI on baPWV are likely due to sex differences that affect arterial stiffness in older overweight and obese individuals.